2010
DOI: 10.1088/0067-0049/190/1/77
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Model Atmosphere Analysis of Cool White Dwarfs in the Sloan Digital Sky Survey

Abstract: We present optical spectroscopy and near-infrared photometry of 126 cool white dwarfs (WDs) in the Sloan Digital Sky Survey (SDSS). Our sample includes high proper motion targets selected using the SDSS and USNO-B astrometry and a dozen previously known ultracool WD candidates. Our optical spectroscopic observations demonstrate that a clean selection of large samples of cool WDs in the SDSS (and the SkyMapper, Pan-STARRS, and the Large Synoptic Survey Telescope data sets) is possible using a reduced proper mot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(147 citation statements)
references
References 65 publications
(152 reference statements)
8
138
1
Order By: Relevance
“…J095051.70+122758.5 looks quite similar, with pronounced band heads at roughly 5600 Å, 5200 Å, and 4700 Å, and is obviously a newly discovered peculiar DQ 3 . J124739.04+064604.5 and J180302.57+232043.3, also classified as peculiar DQs (Kilic et al 2010;Limoges et al 2013;Kleinman et al 2013), look similar to the former two spectra, but display a declining flux density towards the shortest wavelengths. All four stars have significant proper motions between 200 and 400 mas yr .1 .…”
Section: Uncertain Classifications and Possible Contaminationmentioning
confidence: 72%
“…J095051.70+122758.5 looks quite similar, with pronounced band heads at roughly 5600 Å, 5200 Å, and 4700 Å, and is obviously a newly discovered peculiar DQ 3 . J124739.04+064604.5 and J180302.57+232043.3, also classified as peculiar DQs (Kilic et al 2010;Limoges et al 2013;Kleinman et al 2013), look similar to the former two spectra, but display a declining flux density towards the shortest wavelengths. All four stars have significant proper motions between 200 and 400 mas yr .1 .…”
Section: Uncertain Classifications and Possible Contaminationmentioning
confidence: 72%
“…The pure-H models used are those of [14], but now including the red wing opacity from Ly . The pure-He model atmospheres considered are the same models as those used in [5]. The surface gravity is fixed to log g = 8 (the most typical value for white dwarfs).…”
Section: Cool White Dwarf Identificationmentioning
confidence: 99%
“…Blue squares correspond to high proper motion stars in this sample (μ > 100 mas/yr). For the sake of comparison we also show the objects studied in Kilic et al (2010a), confirmed cool white dwarfs as magenta asterisks and subdwarfs that contaminated their sample as green asterisks (IR photometry for the subdwarfs is taken from the 2MASS catalogue, Cutri et al 2003). The solid lines correspond to the theoretical tracks for pure-H composition with tangential velocities of V tan = 40 km s −1 (top) and 160 km s −1 (bottom).…”
Section: Lsr J0745+2627 Identificationmentioning
confidence: 99%
“…3). Asterisks correspond to objects from Kilic et al (2010a): cool white dwarfs are depicted in magenta and subdwarfs in green. Fig.…”
Section: Lsr J0745+2627 Identificationmentioning
confidence: 99%
See 1 more Smart Citation